High-performance modified resin material and preparation method thereof

Through dopamine-modified epoxy resin and nanoparticle @PDA composite material, the rapid curing and strong interface combination of high-performance modified resin is achieved, solving the problem of anti-slip sand peeling and injury paint, and improving the safety and economic benefits of Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro

CN120424567APending Publication Date: 2025-08-05CHONGQINGSHI ZHIXIANG PAVING TECH ENG CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510760752.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

Existing anti-slip sand materials have frequent sand particles falling off in the robo-loading channel, and it is urgent to develop high-performance modified resin materials to improve bonding strength.

Method used

The dopamine-modified epoxy resin and nanoparticle @PDA composite material are used to form a quinone structure by reacting the amino group of dopamine and epoxy group, which catalyzes the thiol-epoxy click reaction, and combine the polythiol flexible chain and the end amino polyether chain to toughen, forming a strong interface bond.

Benefits of technology

The material cures rapidly at low temperatures, improving toughness and impact resistance, solving the problem of anti-slip sand peeling and injury paint, and ensuring the safety and economic benefits of Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-Ro-R

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120424567A_ABST
    Figure CN120424567A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance modified resin material and a preparation method thereof, and belongs to the technical field of resin composite material preparation. The high-performance modified resin material is prepared from a main agent, a curing agent and nano filler, the main agent is prepared from 70 to 100 parts of bisphenol epoxy resin, 20 to 40 parts of dopamine modified epoxy resin, 5 to 15 parts of diglycidyl ether, 3 to 15 parts of flame retardant, 0.3 to 1 part of anti-settling agent, 0.05 to 0.3 part of defoaming agent and 0.1 to 0.5 part of pigment; the curing agent is prepared from the following components in parts by weight: 15-35 parts of a rapid curing agent, 10-30 parts of a toughening curing agent, 5-15 parts of a dopamine modified amine curing agent, 0.5-3 parts of an accelerant and 0.1-0.5 part of an antioxidant; and the nano filler is nano-particle coated PDA (potato dextrose agar). Amino of dopamine reacts with epoxy group, catechol is oxidized to generate a quinoneform structure, thiol-epoxy click reaction is catalyzed, and the material can be rapidly cured at low temperature; a flexible chain (-S-CH-CH-) of polymercaptan and a polyether chain of amine-terminated polyether are synergistically toughened, so that the toughness and impact resistance of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resin composite material preparation, and in particular relates to a high-performance modified resin material and a preparation method thereof. Background Art

[0002] Amidst the continued prosperity of global trade, ro-ro vessels, as efficient means of transporting cargo, are responsible for the maritime transport of a large number of vehicles, containers, and other goods. The anti-slip design of ro-ro ship gangways is a key element in ensuring the safety and stability of vehicles and cargo during the roll-on and roll-off processes. Through its special anti-slip structure and materials, it provides sufficient friction for cargo and transport equipment, effectively preventing collisions and rollovers caused by slippage. This is of great significance for maintaining ship operational safety and reducing economic losses.

[0003] Currently, anti-skid sand material is the primary choice for anti-skid treatment of roll-on / roll-off ship gangways. This composite material, composed of a resin binder and anti-skid gravel, leverages the resin's powerful adhesive properties to firmly adhere the high-friction anti-skid sand particles to the gangway surface, forming a highly anti-skid coating. However, significant deficiencies have emerged in recent years, with frequent incidents of sand shedding and paint damage, leading to numerous complaints from shipowners. The development of high-performance modified resin materials is urgently needed to enhance the bonding strength of anti-skid sand materials and fundamentally address the industry's challenge of sand shedding and paint damage. Summary of the Invention

[0004] In view of this, the object of the present invention is to provide a high-performance modified resin material and a preparation method thereof to solve the above problems.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a high-performance modified resin material, which is composed of a main agent, a curing agent, and a nanofiller; the main agent is composed of 70-100 parts of bisphenol epoxy resin, 20-40 parts of dopamine-modified epoxy resin, 5-15 parts of diglycidyl ether, 3-15 parts of flame retardant, 0.3-1 part of anti-settling agent, 0.05-0.3 part of defoaming agent, and 0.1-0.5 part of pigment; The curing agent is composed of 15-35 parts of a fast curing agent, 10-30 parts of a toughening curing agent, 5-15 parts of a dopamine-modified amine curing agent, 0.5-3 parts of an accelerator and 0.1-0.5 parts of an antioxidant; The nanofiller is nanoparticles@PDA; The weight ratio of the main agent, the curing agent and the nano filler is 100:30-80:5-20.

[0006] Furthermore, the dopamine grafting rate of the dopamine-modified epoxy resin is 5-15%; the bisphenol epoxy resin is at least one of bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and bisphenol S diglycidyl ether; the glycidyl ether is at least one of neopentyl glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and ethylene glycol diglycidyl ether; the flame retardant is at least one of TPP, RDP, BDP, and DOPO; the anti-settling agent is a compound of fumed silica and BYK-P 2710; the defoaming agent is at least one of BYK-066N, BYK-085, and TEGO Foamex 810; and the pigment is black iron oxide.

[0007] Furthermore, the fast curing agent is a polythioether type polythiol; the toughening curing agent is at least one of terminal amino polyether D230, Baxxodur EC 310, polyamide 650, and polyamide 651; the accelerator is at least one of DMAP, DMP-30, BDMA, and DABCO; the antioxidant is composed of a phenolic main antioxidant and a phosphite auxiliary antioxidant in a mass ratio of 1:1, and the phenolic main antioxidant is butylated hydroxytoluene, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)- At least one of 1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid octadecyl; the phosphite auxiliary antioxidant is at least one of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite.

[0008] Furthermore, the dopamine-modified epoxy resin is prepared by the following method: 1-5 wt% dopamine hydrochloride is dissolved in Tris buffer, reacted with bisphenol epoxy resin E51 at 40-80° C. for 2-6 hours, and vacuum dehydrated to obtain dopamine-modified epoxy resin.

[0009] Furthermore, the pH of the Tris buffer is 8.5-9.5.

[0010] Furthermore, the dopamine-modified amine curing agent is prepared by the following method: dissolving dopamine hydrochloride in a Tris buffer solution and adjusting the pH value to 8.5-9.0; then stirring at room temperature for 6-12 hours under nitrogen protection; then adding polyetheramine D400 in a molar ratio of 1:1-1:3 to the oxidized dopamine solution, reacting at 25-40°C for 12-48 hours under nitrogen protection, then adding hydrochloric acid to adjust the pH to neutral, stopping the reaction to obtain a reaction solution; placing the reaction solution into a dialysis bag to remove unreacted dopamine and small molecule byproducts, thereby obtaining a dopamine-modified amine curing agent.

[0011] Furthermore, the nanoparticles are at least one of silicon dioxide, titanium dioxide, and vanadium dioxide.

[0012] Furthermore, a method for preparing a high-performance modified resin material is also included, comprising the following steps: S1. At 30-50°C, mix 70-100 parts of bisphenol epoxy resin, 20-40 parts of dopamine-modified epoxy resin, 5-15 parts of diglycidyl ether, and 3-15 parts of flame retardant for 5-15 minutes, then add 0.3-1 parts of anti-settling agent, 0.05-0.3 parts of defoaming agent, and 0.1-0.5 parts of pigment in sequence until the mixture is uniform to obtain the main agent; S2. Mix 15-35 parts of a fast curing agent, 10-30 parts of a toughening curing agent, 5-15 parts of a dopamine-modified amine curing agent, 0.5-3 parts of an accelerator, and 0.1-0.5 parts of an antioxidant at 30-50° C. for 5-15 minutes until the mixture is uniform, thereby obtaining a curing agent. S3. The nanoparticles were dispersed in Tris buffer and sonicated for 10-30 min. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 12-24 h to form a PDA layer coating the nanoparticles. The mixture was then centrifuged at 6000-10000 rpm / min for 3-5 min. The product was collected to remove unreacted monomers and dried to obtain nanoparticles@PDA. S4. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 5-15 minutes, then add the curing agent and mix them evenly to obtain a high-performance modified resin material; S5. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0013] Furthermore, in step S3, the mass ratio of dopamine hydrochloride to nanoparticles is 1:1-1:5.

[0014] The beneficial effects of the present invention are: The present invention uses the amino group of dopamine to react with the epoxy group, and at the same time its catechol is oxidized to form a quinone structure, which catalyzes the thiol-epoxy click reaction, allowing the material to cure rapidly even at low temperatures; the flexible chain of polythiol (-S-CH2-CH2-) and the polyether chain of the amino-terminated polyether synergistically enhance the toughness and impact resistance of the material; the nanoparticle @PDA filler forms a strong interfacial bond with the resin matrix through the adhesion properties of dopamine; the o-phthalic dihydroxy group in the dopamine molecule can significantly enhance the adhesion between the material and the base surface, effectively solving the problem of anti-skid sand falling off and damaging the paint.

[0015] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to make the purpose, technical solutions and beneficial effects of the invention clearer, the present invention is described with the following drawings: Figure 1 It is a preparation flow chart of the present invention. DETAILED DESCRIPTION

[0017] like Figure 1 As shown, the present invention provides a method for preparing a high-performance modified resin material.

[0018] Example 1 S1. Dissolve 3 wt% of dopamine hydrochloride in a Tris buffer solution with a pH of 9, and then react with bisphenol epoxy resin E51 at 60° C. for 4 h, followed by vacuum dehydration to obtain a dopamine-modified epoxy resin; S2. At 40°C, 85 parts of bisphenol epoxy resin (composed of 40 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 30 parts of dopamine-modified epoxy resin, 10 parts of diglycidyl ether, and 9 parts of flame retardant were mixed for 10 minutes, and then 0.6 parts of anti-settling agent, 0.17 parts of defoaming agent, and 0.3 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent; S3. Dopamine hydrochloride was dissolved in Tris buffer, and the pH value was adjusted to 8.7. The mixture was stirred at room temperature for 9 hours under nitrogen protection, and the solution gradually changed from colorless to light brown. Polyetheramine D400 was then added to the oxidized dopamine solution at a molar ratio of 1:2, and the mixture was reacted at 32°C under nitrogen protection for 30 hours. The color of the solution changed from light brown to dark brown. Hydrochloric acid was then added to adjust the pH value to neutral, and the reaction was stopped to obtain a reaction solution. The reaction solution was placed in a dialysis bag to remove unreacted dopamine and small molecule by-products, thereby obtaining a dopamine-modified amine curing agent. S4. At 40° C., mix 25 parts of polythioether-type polythiol, 20 parts of amino-terminated polyether D230, 10 parts of dopamine-modified amine curing agent, 1.5 parts of DMAP, and 0.3 parts of antioxidant (composed of 0.15 parts of butylated hydroxytoluene and 0.15 parts of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S5. Titanium dioxide was dispersed in Tris buffer and sonicated for 20 minutes. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 18 hours (the mass ratio of dopamine hydrochloride to titanium dioxide was 1:3) to form a PDA layer-coated nanoparticles. The resulting product was then centrifuged at 8000 rpm / min for 4 minutes. The product was collected and washed three times with deionized water to remove unreacted monomers. After drying, nanoparticles@PDA were obtained. S6. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 10 minutes, then add the curing agent (the weight ratio of the main agent, curing agent, and nanofiller is 100:60:15), and mix them evenly to obtain a high-performance modified resin material; S7. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0019] Example 2 S1. Dissolve 3 wt% of dopamine hydrochloride in a Tris buffer solution with a pH of 9, and then react with bisphenol epoxy resin E51 at 60° C. for 4 h, followed by vacuum dehydration to obtain a dopamine-modified epoxy resin; S2. At 40°C, 85 parts of bisphenol epoxy resin (composed of 40 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 30 parts of dopamine-modified epoxy resin, 10 parts of diglycidyl ether, and 9 parts of flame retardant were mixed for 10 minutes, and then 0.6 parts of anti-settling agent, 0.17 parts of defoaming agent, and 0.3 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent; S3. Dopamine hydrochloride was dissolved in Tris buffer, and the pH value was adjusted to 8.7. The mixture was stirred at room temperature for 9 hours under nitrogen protection, and the solution gradually changed from colorless to light brown. Polyetheramine D400 was then added to the oxidized dopamine solution at a molar ratio of 1:2, and the mixture was reacted at 32°C under nitrogen protection for 30 hours. The color of the solution changed from light brown to dark brown. Hydrochloric acid was then added to adjust the pH value to neutral, and the reaction was stopped to obtain a reaction solution. The reaction solution was placed in a dialysis bag to remove unreacted dopamine and small molecule by-products, thereby obtaining a dopamine-modified amine curing agent. S4. At 40° C., mix 25 parts of polythioether-type polythiol, 20 parts of amino-terminated polyether D230, 10 parts of dopamine-modified amine curing agent, 1.5 parts of DMAP, and 0.3 parts of antioxidant (composed of 0.15 parts of butylated hydroxytoluene and 0.15 parts of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S5. Titanium dioxide was dispersed in Tris buffer and sonicated for 20 minutes. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 18 hours (the mass ratio of dopamine hydrochloride to titanium dioxide was 1:3) to form a PDA layer-coated nanoparticles. The resulting product was then centrifuged at 8000 rpm / min for 4 minutes. The product was collected and washed three times with deionized water to remove unreacted monomers. After drying, nanoparticles@PDA were obtained. S6. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 10 minutes, then add the curing agent (the weight ratio of the main agent, curing agent, and nanofiller is 100:60:15), and mix them evenly to obtain a high-performance modified resin material; S7. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0020] The difference between Example 2 and Example 1 is that the ratio of the main agent is different, but both are within the scope of protection of the present invention.

[0021] Example 3 S1. Dissolve 3 wt% of dopamine hydrochloride in a Tris buffer solution with a pH of 9, and then react with bisphenol epoxy resin E51 at 60° C. for 4 h, followed by vacuum dehydration to obtain a dopamine-modified epoxy resin; S2. At 40°C, 70 parts of bisphenol epoxy resin (composed of 30 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 20 parts of dopamine-modified epoxy resin, 5 parts of diglycidyl ether, and 15 parts of flame retardant were mixed for 10 minutes, and then 0.3 parts of anti-settling agent, 0.05 parts of defoaming agent, and 0.5 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent; S3. Dopamine hydrochloride was dissolved in Tris buffer, and the pH value was adjusted to 8.7. The mixture was stirred at room temperature for 9 hours under nitrogen protection, and the solution gradually changed from colorless to light brown. Polyetheramine D400 was then added to the oxidized dopamine solution at a molar ratio of 1:2, and the mixture was reacted at 32°C under nitrogen protection for 30 hours. The color of the solution changed from light brown to dark brown. Hydrochloric acid was then added to adjust the pH value to neutral, and the reaction was stopped to obtain a reaction solution. The reaction solution was placed in a dialysis bag to remove unreacted dopamine and small molecule by-products, thereby obtaining a dopamine-modified amine curing agent. S4. At 40° C., mix 35 parts of polythioether-type polythiol, 10 parts of amino-terminated polyether D230, 15 parts of dopamine-modified amine curing agent, 0.5 parts of DMAP, and 0.5 parts of antioxidant (composed of 0.25 parts of butylated hydroxytoluene and 0.25 parts of bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S5. Titanium dioxide was dispersed in Tris buffer and sonicated for 20 minutes. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 18 hours (the mass ratio of dopamine hydrochloride to titanium dioxide was 1:3) to form a PDA layer-coated nanoparticles. The resulting product was then centrifuged at 8000 rpm / min for 4 minutes. The product was collected and washed three times with deionized water to remove unreacted monomers. After drying, nanoparticles@PDA were obtained. S6. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 10 minutes, then add the curing agent (the weight ratio of the main agent, curing agent, and nanofiller is 100:60:15), and mix them evenly to obtain a high-performance modified resin material; S7. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0022] The difference between Example 3 and Example 1 is that the ratio of the curing agent is different, but both are within the scope of protection of the present invention.

[0023] In order to demonstrate the superiority of the present invention, comparative examples 1 to 3 are provided herein.

[0024] Comparative Example 1 S1. At 40°C, 85 parts of bisphenol epoxy resin (composed of 40 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 10 parts of diglycidyl ether, and 9 parts of flame retardant were mixed for 10 minutes. Then, 0.6 parts of anti-settling agent, 0.17 parts of defoaming agent, and 0.3 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent. S2. Dopamine hydrochloride was dissolved in Tris buffer, the pH value was adjusted to 8.7, and the mixture was stirred at room temperature for 9 hours under nitrogen protection, and the solution gradually changed from colorless to light brown; polyetheramine D400 was then added to the oxidized dopamine solution at a molar ratio of 1:2, and the mixture was reacted at 32°C under nitrogen protection for 30 hours, and the color of the solution changed from light brown to dark brown. Hydrochloric acid was then added to adjust the pH value to neutral and the reaction was stopped to obtain a reaction solution; the reaction solution was placed in a dialysis bag to remove unreacted dopamine and small molecule by-products, and a dopamine-modified amine curing agent was obtained; S3. At 40° C., mix 25 parts of polythioether-type polythiol, 20 parts of amino-terminated polyether D230, 10 parts of dopamine-modified amine curing agent, 1.5 parts of DMAP, and 0.3 parts of antioxidant (composed of 0.15 parts of butylated hydroxytoluene and 0.15 parts of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S4. Titanium dioxide was dispersed in Tris buffer and sonicated for 20 minutes. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 18 hours (the mass ratio of dopamine hydrochloride to titanium dioxide was 1:3) to form a PDA layer-coated nanoparticles. The resulting product was then centrifuged at 8000 rpm / min for 4 minutes. The product was collected and washed three times with deionized water to remove unreacted monomers. After drying, nanoparticles@PDA were obtained. S5. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 5-15 minutes, then add the curing agent (the weight ratio of the main agent, curing agent, and nanofiller is 100:60:15), and mix them evenly to obtain a high-performance modified resin material; S6. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0025] The difference between Comparative Example 1 and Example 1 is that dopamine-modified epoxy resin is not introduced, and the rest are the same.

[0026] Comparative Example 2 S1. Dissolve 3 wt% of dopamine hydrochloride in a Tris buffer solution with a pH of 9, and then react with bisphenol epoxy resin E51 at 60° C. for 4 h, followed by vacuum dehydration to obtain a dopamine-modified epoxy resin; S2. At 40°C, 85 parts of bisphenol epoxy resin (composed of 40 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 30 parts of dopamine-modified epoxy resin, 10 parts of diglycidyl ether, and 9 parts of flame retardant were mixed for 10 minutes, and then 0.6 parts of anti-settling agent, 0.17 parts of defoaming agent, and 0.3 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent; S3. At 40° C., mix 25 parts of polythioether-type polythiol, 20 parts of amino-terminated polyether D230, 1.5 parts of DMAP, and 0.3 parts of an antioxidant (composed of 0.15 parts of butylated hydroxytoluene and 0.15 parts of bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S4. Titanium dioxide was dispersed in Tris buffer and sonicated for 20 minutes. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 18 hours (the mass ratio of dopamine hydrochloride to titanium dioxide was 1:3) to form a PDA layer-coated nanoparticles. The resulting product was then centrifuged at 8000 rpm / min for 4 minutes. The product was collected and washed three times with deionized water to remove unreacted monomers. After drying, nanoparticles@PDA were obtained. S5. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 10 minutes, then add the curing agent (the weight ratio of the main agent, curing agent, and nanofiller is 100:60:15), and mix them evenly to obtain a high-performance modified resin material; S6. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0027] The difference between Comparative Example 2 and Example 1 is that no dopamine-modified amine curing agent is introduced, and the rest are the same.

[0028] Comparative Example 3 S1. Dissolve 3 wt% of dopamine hydrochloride in a Tris buffer solution with a pH of 9, and then react with bisphenol epoxy resin E51 at 60° C. for 4 h, followed by vacuum dehydration to obtain a dopamine-modified epoxy resin; S2. At 40°C, 85 parts of bisphenol epoxy resin (composed of 40 parts of bisphenol A diglycidyl ether and 45 parts of bisphenol S diglycidyl ether), 30 parts of dopamine-modified epoxy resin, 10 parts of diglycidyl ether, and 9 parts of flame retardant were mixed for 10 minutes, and then 0.6 parts of anti-settling agent, 0.17 parts of defoaming agent, and 0.3 parts of pigment were added in sequence and mixed until uniformly mixed to obtain the main agent; S3. Dopamine hydrochloride was dissolved in Tris buffer, and the pH value was adjusted to 8.7. The mixture was stirred at room temperature for 9 hours under nitrogen protection, and the solution gradually changed from colorless to light brown. Polyetheramine D400 was then added to the oxidized dopamine solution at a molar ratio of 1:2, and the mixture was reacted at 32°C under nitrogen protection for 30 hours. The color of the solution changed from light brown to dark brown. Hydrochloric acid was then added to adjust the pH value to neutral, and the reaction was stopped to obtain a reaction solution. The reaction solution was placed in a dialysis bag to remove unreacted dopamine and small molecule by-products, thereby obtaining a dopamine-modified amine curing agent. S4. At 40° C., mix 25 parts of polythioether-type polythiol, 20 parts of amino-terminated polyether D230, 10 parts of dopamine-modified amine curing agent, 1.5 parts of DMAP, and 0.3 parts of antioxidant (composed of 0.15 parts of butylated hydroxytoluene and 0.15 parts of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite) until uniformly mixed to obtain a curing agent; S5. Evenly mix the main agent and curing agent at room temperature (the weight ratio of the main agent to the curing agent is 100:60) to obtain a high-performance modified resin material; S6. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

[0029] The difference between Comparative Example 3 and Example 1 is that nanoparticles@PDA are not added, and the rest are the same.

[0030] The high-performance modified resin materials obtained in Examples 1 to 3, Comparative Examples 1 to 3, and existing resin materials were subjected to performance tests, and the results are as follows: As can be seen from the table above, the high-performance modified resin material prepared according to the method and proportions of the present invention achieves optimal bonding strength with steel plates and impact strength, and can be opened to traffic in approximately 12 hours, saving time. In contrast, the modified resin materials prepared in Comparative Example 1, which does not introduce the dopamine-modified epoxy resin, Comparative Example 2, which does not introduce the dopamine-modified amine curing agent, and Comparative Example 3, which does not add nanoparticles of @PDA, exhibit reduced performance in all aspects and require significantly longer to be opened to traffic.

[0031] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A high-performance modified resin material, characterized by: The high-performance modified resin material is composed of a main agent, a curing agent, and a nanofiller; the main agent is composed of 70-100 parts of bisphenol epoxy resin, 20-40 parts of dopamine-modified epoxy resin, 5-15 parts of diglycidyl ether, 3-15 parts of flame retardant, 0.3-1 parts of anti-settling agent, 0.05-0.3 parts of defoaming agent, and 0.1-0.5 parts of pigment; The curing agent is composed of 15-35 parts of a fast curing agent, 10-30 parts of a toughening curing agent, 5-15 parts of a dopamine-modified amine curing agent, 0.5-3 parts of an accelerator and 0.1-0.5 parts of an antioxidant; The nanofiller is nanoparticles@PDA; The weight ratio of the main agent, the curing agent and the nano filler is 100:30-80:5-20.

2. A high-performance modified resin material according to claim 1, characterized in that: The dopamine grafting rate of the dopamine-modified epoxy resin is 5-15%; the bisphenol epoxy resin is at least one of bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and bisphenol S diglycidyl ether; the glycidyl ether is at least one of neopentyl glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, and ethylene glycol diglycidyl ether; the flame retardant is at least one of TPP, RDP, BDP, and DOPO; the anti-settling agent is a mixture of fumed silica and BYK-P 2710; the defoaming agent is at least one of BYK-066N, BYK-085, and TEGO Foamex 810; and the pigment is black iron oxide.

3. A high-performance modified resin material according to claim 2, characterized in that: The fast curing agent is a polythioether type polythiol; the toughening curing agent is at least one of amino-terminated polyether D230, Baxxodur EC 310, polyamide 650, and polyamide 651; the accelerator is at least one of DMAP, DMP-30, BDMA, and DABCO; the antioxidant is composed of a phenolic primary antioxidant and a phosphite auxiliary antioxidant in a mass ratio of 1:1, and the phenolic primary antioxidant is butylated hydroxytoluene, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)- At least one of 1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid octadecyl; the phosphite auxiliary antioxidant is at least one of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite.

4. A high-performance modified resin material according to claim 2, characterized in that: The dopamine-modified epoxy resin is prepared by the following method: 1-5 wt % dopamine hydrochloride is dissolved in Tris buffer, reacted with bisphenol epoxy resin E51 at 40-80° C. for 2-6 hours, and vacuum dehydrated to obtain the dopamine-modified epoxy resin.

5. A high-performance modified resin material according to claim 4, characterized in that: The pH of the Tris buffer is 8.5-9.

5.

6. The high-performance modified resin material according to claim 1, characterized in that: The dopamine-modified amine curing agent is prepared by the following method: dissolving dopamine hydrochloride in a Tris buffer solution, adjusting the pH value to 8.5-9.0; then stirring at room temperature for 6-12 hours under nitrogen protection; then adding polyetheramine D400 in a molar ratio of 1:1-1:3 to the oxidized dopamine solution, reacting at 25-40° C. under nitrogen protection for 12-48 hours, then adding hydrochloric acid to adjust the pH to neutral, and stopping the reaction to obtain a reaction solution; The reaction solution is placed in a dialysis bag to remove unreacted dopamine and small molecule by-products to obtain a dopamine-modified amine curing agent.

7. The high-performance modified resin material according to claim 1, characterized in that: The nanoparticles are at least one of silicon dioxide, titanium dioxide and vanadium dioxide.

8. The high-performance modified resin material according to any one of claims 1 to 7, further comprising a method for preparing the high-performance modified resin material, characterized in that: The following steps are included: S1. At 30-50°C, mix 70-100 parts of bisphenol epoxy resin, 20-40 parts of dopamine-modified epoxy resin, 5-15 parts of diglycidyl ether, and 3-15 parts of flame retardant for 5-15 minutes, then add 0.3-1 parts of anti-settling agent, 0.05-0.3 parts of defoaming agent, and 0.1-0.5 parts of pigment in sequence until the mixture is uniform to obtain the main agent; S2. Mix 15-35 parts of a fast curing agent, 10-30 parts of a toughening curing agent, 5-15 parts of a dopamine-modified amine curing agent, 0.5-3 parts of an accelerator, and 0.1-0.5 parts of an antioxidant at 30-50° C. for 5-15 minutes until the mixture is uniform, thereby obtaining a curing agent. S3. The nanoparticles were dispersed in Tris buffer and sonicated for 10-30 min. Dopamine hydrochloride was then added and magnetically stirred at room temperature for 12-24 h to form a PDA layer coating the nanoparticles. The mixture was then centrifuged at 6000-10000 rpm / min for 3-5 min. The product was collected to remove unreacted monomers and dried to obtain nanoparticles@PDA. S4. Mix the main agent and nanoparticles @PDA in proportion at room temperature, disperse them ultrasonically for 5-15 minutes, then add the curing agent and mix them evenly to obtain a high-performance modified resin material; S5. Apply to the steel plate base after vacuum degassing and cure at 25℃ for 24 hours before performance test.

9. The method for preparing a high-performance modified resin material according to claim 8, characterized in that: In step S3, the mass ratio of dopamine hydrochloride to nanoparticles is 1:1-1:5.

Citation Information

Cited By

  • Protective coating with inversely enhanced adhesive force as well as preparation method and application of protective coating

    CN122234688A

  • A protective coating with reverse enhanced adhesion and its preparation method and application

    CN122234688B